Accessory head of sternocleidomastoid-a case report - Barma Deb Saranva; Rabha Gunamani; Talukdar Kunjalal (Wolters Kluwer Medknow Publications, 2015)
As many important nerves emerge from the posterior border of sternocleidomastoid (SCM), it is important to know the morphological anatomy of sternocleidomastoid for surgical as well as radiological purpose. During routine dissection of head and neck for student demonstration, an accessory head of sternocleidomastoid was found arising from the superior surface of the middle third of the clavicle on the right side of the neck. Sternocleidomastoid is a key landmark as it divides the neck into anterior and lateral regions (anterior and posterior triangles respectively. Morphological variations arise due to the complexity of sequential development of any region. SCM is an important surgical landmark for clinicians. A well versed knowledge of its variations can avoid diagnostic and surgical complications.